New species of Macrophyllodromia (Blattaria, Blattellidae) from Ecuador and a key to males of the genus - Vidlička, Ľubomír (Zootaxa, 2013)
Representatives of the cockroach genus Macrophyllodromia are widely distributed in Central and South Americas. The genus involves 10 species, including one new species described here, that are divided into 3 species groups—splendida, amabile and maximiliani. Macrophyllodromia onorei sp. n. is described as the fourth species of this genus from Ecuador. A key is provided for males of all known species of Macrophyllodromia and a species distribution map is presented.